Relating behavioural intentions towards collaborative discussions and language performance of ESL online game players in MMORPG context - Rino Shafierul Azizie Shahrir Raghbir; Lee, Luan Ng; Shin, Yi Chew (Penerbit Universiti Kebangsaan Malaysia, 2025)
With the advancement of Massively Multiplayer Online Role-Playing Games (MMORPGs), there has been an increase in the number of ESL learners who are involved in online games. However, there is a lack of empirical studies that focused on the impact of MMORPGs on ESL learners’ language performance and their behavioural intentions related to collaborative discussions. Therefore, this study aims to investigate the impact of learners’ behavioural intentions towards collaborative discussions and their language performance through playing MMORPGs. Using a mixed methods approach, 16 online ESL game players were invited to play MMORPG for 15 hours. The changes in language performance of online ESL game players were based on pre- and post-language tests. A 5-point Likert scale questionnaire was used to assess the participants’ intentions towards collaborative discussions in online gameplay. The players' interactions during gameplay were also video recorded and analysed to capture instances of collaborative discussions. The findings indicate that participants with high intentions towards engaging in collaborative discussions seem to show a higher frequency of participation in collaborative discussions and scored higher in both language tests. The results revealed that these players’ intentions to engage in collaborative discussions do influence their language learning behaviour and their language performance. This study highlights how the MMORPG context could incentivise ESL learners’ engagement in collaborative discussions, which inherently impacts their English language performance through verbal exchanges during gameplay sessions that mirror authentic language use.